2022
DOI: 10.1136/bmj-2021-069848
|View full text |Cite
|
Sign up to set email alerts
|

Changing the assortment of available food and drink for leaner, greener diets

Abstract: Theresa Marteau and colleagues discuss the potential of “availability interventions” to improve diets and reduce inequalities

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 51 publications
3
17
0
Order By: Relevance
“…Patterning observed in some studies has been consistent with potential differential impact of availability interventions by SEP, suggesting those with higher SEP may be more likely to respond to increased healthier food availability, but with insufficient power to test effects [ 2 , 16 ]. Establishing the mechanisms that might underlie the impact of availability may help establish how best to implement this promising intervention [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patterning observed in some studies has been consistent with potential differential impact of availability interventions by SEP, suggesting those with higher SEP may be more likely to respond to increased healthier food availability, but with insufficient power to test effects [ 2 , 16 ]. Establishing the mechanisms that might underlie the impact of availability may help establish how best to implement this promising intervention [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The promise of so-called 'availability' interventions that change proportions of unhealthy (relative to more healthy) products, is highlighted by an emerging evidence base in relation to food 5 . A Cochrane systematic review found that reducing the proportion of available food products of a certain type (e.g., unhealthy snacks) resulted in markedly reduced selection of those foods 7 , although the included evidence was limited in both quality and quantity.…”
Section: Introductionmentioning
confidence: 99%
“…More recent field trials also suggest that decreasing the proportion of higher energy or meat-based foods reduces their consumption [8][9][10][11] . In terms of alcohol products, there is an absence of evidence, with no eligible studies identified in the aforementioned Cochrane review 7 or in a recent search update 5 . In what is, to our knowledge, the only previous study that has examined the potential of such an intervention applied to alcohol, the proportion of participants selecting an alcoholic drink decreased from 74% when one-quarter of the available drinks were non-alcoholic, to 51% when three-quarters were non-alcoholic 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Availability interventions involve altering the number of instances of a product within the physical micro-environment. These interventions represent a paradigmatic example of micro-environmental interventions that have shown promising evidence of effectiveness [ 10 , 11 ]. The mechanism by which these interventions operate is not fully known.…”
Section: Introductionmentioning
confidence: 99%